Rediscovery and redescription of the Andean earth-snake Atractus wagleri (Reptilia: Serpentes: Colubridae) - Passos, Paulo; Arredondo, Juan C. (Zootaxa, 2009)
Atractus wagleri was described based on a single specimen from Humbo, Department of Boyacá on the western Cordillera Oriental of Colombia, and since its original description there is no further record for the species. In the course of examination of Colombian collections the holotype of the Atractus wagleri could not be found and it is probable that it was lost, but we found three additional specimens of this poorly known snake from localities relatively close to the type locality. In this paper, we describe these specimens, and report data on meristics, morphometrics, and hemipenial variation for the species.